Intrauterine growth restriction in piglets modulates postnatal immune function and hepatic transcriptional responses independently of energy intake - Amdi, C.; Larsen, C.; Jensen, K. M. R.; Tange, E. Ø.; Sato, H.; Williams, A. R. (Frontiers in Physiology, 2023)
Introduction: Insufficient prenatal nutrition can affect fetal development and lead to intrauterine growth restriction (IUGR). The aim of this study was to investigate hepatic transcriptional responses and innate immune function in piglets suffering from IUGR compared to normal-sized piglets at 3 days of age and explore whether the provision of an energy-rich supplement at birth could modulate these parameters. Methods: A total of 68 piglets were included in the study. Peripheral blood mononuclear cells were harvested for LPS stimulation, and organs were harvested post-mortem to quantify relative weights. Liver tissue was utilized for RNA sequencing coupled with gene-set enrichment analysis. Results: IUGR resulted in increased expression of genes such as PDK4 and substantial alterations in transcriptional pathways related to metabolic activity (e.g., citric acid and Krebs cycles), but these changes were equivalent in piglets given an energy-rich supplement or not. Transcriptomic analysis and serum biochemistry suggested altered glucose metabolism and a shift toward oxidation of fatty acids. IUGR piglets also exhibited suppression of genes related to innate immune function (e.g., CXCL12) and pathways related to cell proliferation (e.g., WNT and PDGF signaling). Moreover, they produced less IL-1β in response to LPS stimulation and had lower levels of blood eosinophils than normal-sized piglets. Discussion: Taken together, our results indicate that IUGR results in early-life alterations in metabolism and immunity that may not be easily restored by the provision of exogenous energy supplementation.